2009
DOI: 10.1007/978-3-642-03915-7_31
|View full text |Cite
|
Sign up to set email alerts
|

Improving Time Series Forecasting by Discovering Frequent Episodes in Sequences

Abstract: Abstract. This work aims to improve an existing time series forecasting algorithm -LBF-by the application of frequent episodes techniques as a complementary step to the model. When real-world time series are forecasted, there exist many samples whose values may be specially unexpected. By the combination of frequent episodes and the LBF algorithm, the new procedure does not make better predictions over these outliers but, on the contrary, it is able to predict the apparition of such atypical samples with a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It can be concluded that there exist few works based on KNN to forecast time series, which have mainly been assessed by means of diverse distance metrics in order to identify univariate time series motifs or episodes in the historical data [91]. …”
Section: Related Workmentioning
confidence: 99%
“…It can be concluded that there exist few works based on KNN to forecast time series, which have mainly been assessed by means of diverse distance metrics in order to identify univariate time series motifs or episodes in the historical data [91]. …”
Section: Related Workmentioning
confidence: 99%
“…As a case study, the markets of New York, Australia, and the Iberian Peninsula were examined. An early version of this algorithm can be found in [14].…”
Section: Related Workmentioning
confidence: 99%